2014
DOI: 10.1111/joss.12083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Global and Individual Reproducibility of Projective Mapping with Consumers

Abstract: 19The popularity of projective mapping with consumers for sensory characterization has 20 markedly increased in the last five years. To have confidence in this methodology it is 21 necessary to ensure that a similar product profile would emerge if the test was repeated. 22Also, deciding whether the study should be replicated or not is a key issue in test 23 implementation. In this context, the aim of the present work was to evaluate global and 24 individual reproducibility of projective mapping for sensory cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…However, RV interpretations and comparisons with other studies should be done with care since both the data dimensionality and the size of difference among the products have an impact on this index. This stress yet highlighted need of other criteria less sensitive and more suitable than the RV, but also than the modified RV (or RV2), to measure similarity between data matrices (Ares et al, 2014;Tomic et al, 2013;Vidal et al, 2014). Anyway, in this experiment, a similar five groups partitioning was found for both panels (RI = 0.88).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, RV interpretations and comparisons with other studies should be done with care since both the data dimensionality and the size of difference among the products have an impact on this index. This stress yet highlighted need of other criteria less sensitive and more suitable than the RV, but also than the modified RV (or RV2), to measure similarity between data matrices (Ares et al, 2014;Tomic et al, 2013;Vidal et al, 2014). Anyway, in this experiment, a similar five groups partitioning was found for both panels (RI = 0.88).…”
Section: Discussionmentioning
confidence: 67%
“…From different studies, Vidal, Silva Cadena, and Correa (2014) reported that ''the minimum RV value that has been considered as indicator of good agreement between sample configurations ranges from 0.65 to 0.85''. They also argued that if two mappings of same products return a significant RV, then it can be concluded that information gathered in the two mappings is similar.…”
Section: Sorting Analysismentioning
confidence: 99%
“…The procedures and evaluated criteria to validate the HTM/HRT were based on validation studies of sensory methodologies (Boutrolle et al, ; Lima Filho et al, ; Louw et al, ; Pagès & Husson, ; Saldamando et al, ; Silva, Minim, Silva, Gonçalves et al, ; Vidal et al, ; Worch, Crine, Gruel, & Lê, ; Worch, Lê, Punter, & Pagès, ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the cookies could be a more complex product that has more sensory moduli than that of plain yogurt. As products increase their number of sensory moduli, it is harder for consumers or untrained panelists to adequately describe them (Vidal et al, ). Future studies need to be completed to identify which products are suitable for use with the PAE method.…”
Section: Resultsmentioning
confidence: 99%